Arithmetic fuchsian groups and space time block codes - Carvalho, Edson Donizete de [UNESP]; Andrade, A.A. [UNESP]; Palazzo Jr., R.; Vieira Filho, Jozué [UNESP] (Sociedade Brasileira de Matemática Aplicada e Computacional, 2011)
In the context of space time block codes (STBCs) the theory of arithmetic Fuchsian groups is presented. Additionally, in this work we present a new class of STBCs based on arithmetic Fuchsian groups. This new class of codes satisfies the property full-diversity, linear dispersion and full-rate. Mathematical subject classification: 18B35, 94A15, 20H10.
Keywords: Arithmetic Fuchsian group; division algebra; quaternion order and space time codes